Enhanced selective sonosensitizing efficacy of ultrasound-based anticancer treatment by targeted gold nanoparticles. (December 2016) - Brazzale, Chiara; Canaparo, Roberto; Racca, Luisa; Foglietta, Federica; Durando, Gianni; Fantozzi, Roberto; Caliceti, Paolo; Salmaso, Stefano; Serpe, Loredana
Aim: This study investigates cancer targeted gold nanoparticles as ultrasound sensitizers for the treatment of cancer.Methods: The ultrasound sensitizer activity of folate-PEG decorated gold nanoparticles (FA-PEG-GNP) has been studied on human cancer cell lines that overexpress folate receptors (KB and HCT-116) and another that does not (MCF7), at two ultrasound energy densities (8 × 10 -6 J cm -2 and 8 × 10 -5 J cm -2, for 5 min at 1.866 MHz).Results: FA-PEG-GNP selectively targeted KB and HCT-116 cells and a remarkable reduction in cancer cell growth was observed upon ultrasound exposure, along with significant reactive oxygen species generation and increase in necrotic cells.Conclusion: The combined use of targeting capacity and the ultrasound sensitizing effect, make FA-PEG-GNP promising candidates for the site-specific cancer treatment.